Financial Ratio Analysis at PT. Indocement Tunggal Prakarsa Tbk. Registered on The Indonesia Stock Exchange for the 2016 - 2020 Period - Silvy Kartikasari; Dedi Karmana; Sakti Muda Nasution; Mira Ismirani Fudsy (Majalah Bisnis & IPTEK, 2023)
The present study investigates the evaluation of financial ratios, encompassing liquidity, solvency, and profitability ratios, at PT. Indocement Tunggal Prakarsa Tbk., a company listed on the Indonesia Stock Exchange, by analyzing financial reports spanning the period of 2016–2020. The present study employs a quantitative research methodology whereby the collected data is subjected to analysis in order to facilitate comprehension and interpretation through explanatory means. Upon conducting an analysis and subsequent discussion, the authors concluded that the assessment of financial ratios at PT. Indocement Tunggal Prakarsa Tbk. from 2016 to 2020 is primarily founded on liquidity and solvency ratios. The results indicate that the company's financial standing is generally favorable—the profitability ratios of PT. Indocement Tunggal Prakarsa Tbk. from 2016 to 2020, as analyzed through financial ratio analysis, indicates an average unfavorable state.